Bovine enzootic haematuria from consumption of Pteris deﬂexa and Pteris plumula in northwestern Argentina - Micheloud, Juan Francisco (2017)
Bovine enzootic haematuria (BEH) is caused by prolonged ingestion of toxic principles of bracken fern, essentiallybyPteridium spp. In northwestern Argentina, this disease has a greateconomic impact ant it is attributed a chronic consumption to Pteridium arachnoideum. This paper describes two endemic areas for enzootic hematuria due to the consumption of Pteris deﬂexa and Pteris plumula. Two areas where P. deﬂexa and P. plumula are endemic, but free of Pteridium species, were devised and seven farms were visited. The disease was conﬁrmed basedon the presence of clinicallyaffected animals. Infournecropsies bleeding neoplastic lesions were observed in the mucosa of the urinary bladder. At phytochemical analysis, both ptaquiloside and pterosin B were found in P. deﬂexa and P. plumula. Thus, the consumption of P. deﬂexa and P. plumula can also cause BEH.